Систематичне дослідження протонного розпаду надважких елементів - Srinivas, M.G.; Manjunatha, H.C.; Sridhar, K.N.; Raj, A.C.; Damodara Gupta, P.S. (Publishing house "Academperiodika", 2022)
We have studied the proton decay in almost all superheavy nuclei with atomic number Z = 104–126. We have calculated the energy released during the proton decay (QP), penetration factor (P), normalization factor (F), and the proton decay half-lives. The latter are also longer than that of other decay modes such as the alpha decay and spontaneous fission. The competition of the proton decay with different decay modes reveals that the proton decay is not the dominant decay mode in the superheavy nuclei region. This means that superheavy nuclei are stable against the proton decay.